Influence of Geometric Characteristics of the Flow Pass of Axial Fan on the Pressure Difference Created by It - Gritsenko, Nikita; Goloschapov, Vladimir (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
<span style="color: black; font-family: 'Times New Roman'; font-size: 9pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: UK; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-GB">This scientific paper describes numerical and experimental investigation of the influence produced by a shape of the flow pass of axial fan on the level of created pressure difference. Conical, cylindrical, cylindrical and conical, sphero-conical and other types of the shape of flow pass were investigated. Ultimate values of the levels of created pressure difference were defined provided that a high efficiency factor was retained for axial mine fans designed for the local ventilation of a full scale production. Recommendations on the use of some types of shapes of the flow pass for big axial fans of a high capacity were given to reduce specific quantity of metal and increase the efficiency in a wide range of operation modes. Investigation of the flow pass of the fan designed for the main local ventilation carried out using the 3D flow simulation and the experimental check showed an apparent advantage of the fan with the taper sleeve (flow pass with the meridional flow acceleration) in comparison with cylindrical meridional by-passes used at the present time. A total maximum pressure increment was 20 to 25 % and the maximum output increment was 20 to 30 %. First of all, this is related to a convergent behavior of the flow stream in the meridional plane, which results in a decrease of the influence of separated flows.